Microstructure and Mechanical Properties of P-Modified Al–25Mg2Si–6Mg–11Cu–11Zn Alloy - Jeon, Jungmin; Park, Seonghyun; Shin, Eunjoo; Lim, Jae-Won; Jung, Jae-Gil (Archives of Metallurgy and Materials, 2026)
We study the microstructure and precipitation behavior of P-modified Al–25Mg2Si alloy with excess Mg, Cu, and Zn. The addition of P significantly refines the primary Mg2Si phase from 165 to 43 μm due to enhanced heterogeneous nucleation at the Mg3P2 phase. This refinement leads to improvements in compressive strength from 440 to 585 MPa and fracture strain from 3.0 to 3.6%. The solution-treated alloy containing partially spheroidized and smoothed secondary phases exhibits significant age hardening at both 25°C and 120°C. Transmission electron microscopy (TEM) and small-angle neutron scattering (SANS) analyses confirm the formation of Guinier-Preston (GP) zones, η', and η nanoprecipitates during aging at 120°C. Solution and subsequent peak-aging enhance the compressive strength from 585 to 722 MPa and fracture strain from 3.6 to 4.0% of the alloy.